Time to recovery from neonatal sepsis and its determinants among neonates admitted in Woldia comprehensive specialized hospital, Northeast Ethiopia: a retrospective cohort study - Kassawmar Ambaye; Ali Yimer; Esuyawkal Mislu; Zeru Wendimagegn; Henok Kumsa (Frontiers Media S.A., 2024)
BackgroundNeonatal sepsis is the most serious problem in neonates. It is the leading cause of neonatal death in developing countries, particularly in sub-Saharan Africa. The Ethiopian 2016 Demographic Health Survey report revealed that a high number of neonatal deaths are associated with neonatal sepsis. However, limited studies are available on exposure and time to recovery inferences in Ethiopia. Therefore, this study aimed to assess the time to recovery from neonatal sepsis and its determinants among neonates admitted to Woldia Comprehensive Specialized Hospital (WCSH), Northeast Ethiopia.MethodsA retrospective cohort study was conducted, including 351 neonates, using systematic random sampling at WCSH from 7 to 30 March 2023. The data were entered into Epi data version 4.6 and exported to STATA 14 for analysis. Cox regression was used to identify the determinants of time to recovery from neonatal sepsis, and a variable with a p-value of less than 0.05, was used to declare significant association at a 95% confidence interval.ResultAmong 351 neonates with sepsis, 276 (78.63%) recovered, and the median time to recovery was 6 days. Induced labor (AHR = 0.54, 95% CI: 0.369, 0.78) and resuscitation at birth (AHR = 0.7, 95% CI: 0.51, 0.974) were significantly associated with the recovery time of neonatal sepsis.Conclusions and recommendationThe time to recovery from neonatal sepsis is comparable to previous studies' results. The 25th and 75th percentiles were 4 and 8 days, respectively. Health professionals working in the NICU need to pay special attention to neonates born from mothers who had induced labor and those who were resuscitated at birth.